Resistance Of Competency Knowledge Acquisition In Service Industry Professionals - Yoke-Chin, Cheng (2009)
This research seeks to understand factors that prevent professionals in service industry toward competency knowledge acquisition. Results of the present study indicates that technology advancement, work process management and individualistic are the factors in causing professionals in service industry to resist competency knowledge acquisition. However, factor form socioeconomic does not contribute to the resistance of competency knowledge acquisition by professionals in service industry.